Cobalamin Levels in Fish and Fortified Milk Substitutes - Motta, Carla (2021)
Objectives: Natural forms of vitamin B12, methylcobalamin (MeCbl), and hydroxocobalamin (OHCbl) are bioidentical to the forms occurring in human physiology and animal foods. However, in fortified foods, different vitamers can be present including cyanocobalamin (CNCbl), a synthetic form that can be problematic due to cyanide content. The main goal of this work is to identify the different vitamin B12 vitamers (CNCbl, MeCbl, and OHCbl) in fish and in fortified soy milk to characterize the different types of cobalamins present in natural and fortified foods.